Teaching Evidence-Based Practice to MSN, DNP and PhD students: Lessons Learned. - McNeill, Cynthera; George, Nancy; Stephens, Umeika; Walker, Tara (ABNFF Journal, 2024)
Background: An evidence-based practice (EBP) course containing Master of Nursing (MSN), Doctor of Nursing Practice (DNP) and Doctor of Philosophy (PhD) nursing students (N=76) was offered during a 12-week Spring/Summer semester. The intent of this evaluation is to assess the effectiveness and feasibility of a combined graduate level EBP course. Method: A pre-posttest design was used. Anonymous, de-identified demographic questions and the Student Evidence Based Practice Questionnaire (SEBPQ) were used for data collection. Results: The results indicated a significant difference pre vs post course in the areas of EBP use (Sig <0.001; F 15.806), EBP Skill (Sig <0.001, F 43.250) and EBP Communication (Sig <0.001; F 27.566). However, 22 out of the 24 students that reported feeling overwhelmed by the course were MSN students (91.7%). Conclusion: The facilitation, evaluation, and redesign of EBP curriculum need to be informed by data gathered from formal assessments.